Clonally Related Plasmablastic Lymphoma Simultaneously Occurring with Diffuse Large B-Cell Lymphoma - Hashimoto, Norisato; Ueda, Tomoki; Hiraiwa, Shinichiro; Tajiri, Takuma; Nakamura, Naoya; Yokoyama, Kenji (Case Reports in Hematology, 2020)
Plasmablastic lymphoma (PBL) is a rare aggressive lymphoma. Although it was first described in HIV- (human immunodeficiency virus-) infected patients, PBL has been diagnosed in patients with other immunodeficiencies as well as in immunocompetent patients. PBL immunohistochemically expresses plasmacytic markers and lacks pan B-cell markers. The cells of origin of PBL are considered to be plasmablasts. MYC gene rearrangement and MYC overexpression are frequently found in PBL, but the pathogenesis of PBL is yet to be elucidated. Here, we report a case of composite lymphoma of PBL and diffuse large B-cell lymphoma (DLBCL); that is, PBL in the urinary bladder and DLBCL in the nasal cavity occurred simultaneously. We extracted DNA from the two lymphomas for polymerase chain reaction and sequenced the amplified immunoglobulin heavy variable genes and the complementarity-determining region- (CDR-) 3. The sequence of the CDR3 region of both tumors matched. MYC rearrangement was found in the bladder tumor but not in the nasal tumor. The patient was treated with R-CHOP (rituximab, cyclophosphamide, vincristine, doxorubicin, and prednisone), and durable remission had been obtained. The results of the DNA analysis indicated that both PBL and DLBCL emerged from common postgerminal B cells. This case may help to elucidate the pathogenesis of PBL.